2016
DOI: 10.1113/jp272191
|View full text |Cite
|
Sign up to set email alerts
|

Adrenaline release evokes hyperpnoea and an increase in ventilatory CO2 sensitivity during hypoglycaemia: a role for the carotid body

Abstract: Key pointsr Hypoglycaemia is counteracted by release of hormones and an increase in ventilation and CO 2 sensitivity to restore blood glucose levels and prevent a fall in blood pH.r The full counter-regulatory response and an appropriate increase in ventilation is dependent on carotid body stimulation.r We show that the hypoglycaemia-induced increase in ventilation and CO 2 sensitivity is abolished by preventing adrenaline release or blocking its receptors.r Physiological levels of adrenaline mimicked the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(84 citation statements)
references
References 59 publications
6
78
0
Order By: Relevance
“…Through intravenous adrenaline infusion, Thompson et al . () found that adrenaline mirrored the effects caused by hypoglycaemia, increasing both ventilation and CO 2 sensitivity. However, when adrenaline was infused after bilateral carotid sinus nerve section, the rise in minute ventilation was significantly attenuated and P aC O2 was found to be higher compared with control, denoting a clear ventilation–metabolism mismatch.…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…Through intravenous adrenaline infusion, Thompson et al . () found that adrenaline mirrored the effects caused by hypoglycaemia, increasing both ventilation and CO 2 sensitivity. However, when adrenaline was infused after bilateral carotid sinus nerve section, the rise in minute ventilation was significantly attenuated and P aC O2 was found to be higher compared with control, denoting a clear ventilation–metabolism mismatch.…”
mentioning
confidence: 91%
“…Another notable contribution of the study of Thompson et al . () is that their results point towards the existence of a bidirectional link between adrenaline and carotid body. It is well known, as eluded to above, that carotid body activation increases adrenaline release through the sympathoadrenal axis.…”
mentioning
confidence: 92%
See 3 more Smart Citations